Инновации и современные технологии воспитания подрастающего поколения - Скалозубова, Г.В.; Абенова, М.Б. (My University, 2013)
One of main objectives of higher educational institutions of Kazakhstan is preparation of the competitive expert with the higher education, possessing qualities and the properties demanded in the conditions of the market, capable to put and reach personally significant purposes which camps will promote economy development. In this article questions of educational work of higher education institution in seven directions are considered: ideological, the relation of students to study, patriotic, ZOZh formation, legal, spiritually –moral and semeyno – household.